Quality Management System and its Role in the Quality Maturity of Training Hospitals - Homa Seyedi; Rafat Mohebbifar; Sima Rafiei (Iran University of Medical Sciences, 2019)
Background: Recent trends have led many organizations to use strategic planning for designing and implementing Total Quality Management (TQM) as a fundamental necessity. This study investigated the role of TQM in the quality maturity of hospitals from the employees' point of view.  Methods: A cross-sectional study was conducted among the senior managers and officials of three Zanjan University of Medical Sciences (ZUMS) training hospital wards, including supervisors, matrons, and all hospital committee members. All the managers who were willing to participate and met the inclusion criteria were recruited. Two questionnaires, including TQM Assessment and Quality Maturity of Hospital Services were used. Statistical analyses were conducted by SPSS through multivariable regression modeling.  Results: The obtained results affirmed a significant effect of TQM on the quality improvement of hospital services; a unit of increase in the mentioned variable resulted in 0.63 unit of change in quality maturity (P<0.05). Furthermore, among the different aspects of the quality management system, the most significant impact on quality maturity belonged to having a system-wide approach toward management (β=0.342). Conclusion: To improve the quality of hospital services, it is necessary to promote managers and employees' commitment toward the necessity of effectively implementing quality improvement programs. Establishing a process management approach, developing a culture of continuous improvement, adopting a systematic approach to control managerial issues, and encouraging employees to participate in quality improvement goals are necessary in this regard.